The Influence of Independent Curriculum Management on the Development of Students' Pancasila Student Profile Character - Neng Gustini; Nifasri; Neneng Siti Nurushobah (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2024)
The shift in Indonesia’s national curriculum demands a stronger emphasis on character education aligned with the values of the Pancasila Student Profile. The Independent Curriculum, initiated by Nadiem Makarim, offers flexibility and student-centered learning, aiming to nurture students’ potential and interests while fostering character development. This study aims to: (1) Identify the implementation of Independent Curriculum management in SMAIT schools across Cicalengka District; (2) Describe the formation of Pancasila Student Profile character traits among students; and (3) Analyze the influence of curriculum management on character development. A quantitative approach with an ex post facto method was employed. The sample consisted of 30 students selected through purposive sampling. Data were collected via questionnaires and analyzed using SPSS 25, including validity and reliability testing, simple linear regression, and t-test. The findings show: (1) Independent Curriculum management is categorized as high, with an average score of 3.42; (2) Character formation of students aligns with Pancasila values, also in the high category with an average score of 3.45; and (3) Curriculum management has a significant influence of 41% on character development, with a t-value of 4.408 > t-table 1.65 and significance value of 0.00 < 0.05. It is concluded that the management of the Independent Curriculum has a positive and significant effect on the formation of students' Pancasila-based character traits.